Towards simultaneous recognition, localization and mapping for hand-held and wearable cameras - Castle, R; Gawley, D; Klein, G; Murray, D; IEEE (2007)
This paper presents a system which combines single-camera SLAM (Simultaneous Localization and Mapping) with established methods for feature recognition. Besides using standard salient image features to build an on-line map of the camera's environment, this system is capable of identifying and localizing known planar objects in the scene, and incorporating their geometry into the world map. Continued measurement of these mapped objects improves both the accuracy of estimated maps and the robustness of the tracking system. In the context of hand-held or wearable vision, the system's ability to enhance generated maps with known objects increases the map's value to human operators, and also enables meaningful automatic annotation of the user's surroundings. The presented solution lies between the high order enriching of maps such as scene classification, and the efforts to introduce higher geometric primitives such as lines into probabilistic maps. © 2007 IEEE.